2022
DOI: 10.2147/dmso.s320909
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Well-Being, Coping Styles, Perception of Self-Influence on the Diabetes Course and Sociodemographic Characteristics with HbA1c and BMI Among People with Advanced Type 2 Diabetes Mellitus

Abstract: Purpose Assessment of the relationship between psychological and sociodemographic factors with the levels of glycated hemoglobin (HbA1c) and Body Mass Index (BMI) among people with advanced type 2 diabetes mellitus (T2DM). Patients and Methods A total of 2574 persons, among them 1381 (53.7%) women, with type 2 diabetes, during the period of switching from biphasic mixtures of human insulin to insulin analogues. The age of participants ranged from 22 to 94 years (M = 63.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…However, it was in the group of obese patients that a statistically significant decrease in HbA1c concentration, by 0.2%, after MLD therapy was observed. Although the level of HbA1c was within the reference range, the decrease in the value seemed to be of clinical significance, which was confirmed by the research of other authors [ 20 , 44 , 45 , 46 ]. In a prospective study conducted on 4662 subjects, the lowest mortality rate was demonstrated in subjects with HbA1c levels below 5%.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, it was in the group of obese patients that a statistically significant decrease in HbA1c concentration, by 0.2%, after MLD therapy was observed. Although the level of HbA1c was within the reference range, the decrease in the value seemed to be of clinical significance, which was confirmed by the research of other authors [ 20 , 44 , 45 , 46 ]. In a prospective study conducted on 4662 subjects, the lowest mortality rate was demonstrated in subjects with HbA1c levels below 5%.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, it has been estimated that in subjects with HbA1c levels between 5–7%, lowering the average HbA1c concentration by 0.1% may prevent an excessive number of deaths by as much as 12%, or as much as 25% if the concentration is reduced by 0.2% [ 20 ]. Moreover, studies conducted so far have shown that a decrease in HbA1c levels reduces the risk of developing chronic vascular complications [ 45 , 46 ]. Therefore, it is very important to strive for normal HbA1c values in patients with abnormal body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, in a previous study, a similar set of variables accounted for only 7% of variance of HbA 1c levels and 3% of variance of BMI. 28 It was shown that, considering psychological factors, the strongest relationships were between well-being (lower risk of depression) and the number of complications. Namely, the better the well-being, the fewer complications of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“… 25 A previous article presents the relationship between well-being, coping styles, perception of self-influence on the diabetes course as well as sociodemographics with HbA1c and BMI among people with advanced type 2 diabetes. 28 This study is the second part of the data analysis and focuses on factors related to the number of diabetes complications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation